2002
DOI: 10.1243/14680870260189280
|View full text |Cite
|
Sign up to set email alerts
|

Performance and heat release analysis of a pilot-ignited natural gas engine

Abstract: The influence of engine operating variables on the performance, emissions and heat release in a compression ignition engine operating in normal diesel and dual-fuel modes (with natural gas fuelling) was investigated. Substantial reductions in NOx emissions were obtained with dual-fuel engine operation. There was a corresponding increase in unburned hydrocarbon emissions as the substitution of natural gas was increased. Brake specific energy consumption decreased with natural gas substitution at high loads but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…For the dual fuel case there is the added complexity that the mass of the burned zone will also be a function of the mass of gaseous fuel that has been burned during each time step. In order to express this, it is assumed that combustion occurs at a stoichiometric air fuel ratio (AFRs) [3,21,22]. The AFRs has two hydrocarbon fuel components with molecular formulas of C xd H xd and C xg H g ; and the mass ratio of the two fuels is also known.…”
Section: Heat Release Rate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the dual fuel case there is the added complexity that the mass of the burned zone will also be a function of the mass of gaseous fuel that has been burned during each time step. In order to express this, it is assumed that combustion occurs at a stoichiometric air fuel ratio (AFRs) [3,21,22]. The AFRs has two hydrocarbon fuel components with molecular formulas of C xd H xd and C xg H g ; and the mass ratio of the two fuels is also known.…”
Section: Heat Release Rate Analysismentioning
confidence: 99%
“…This description of the combustion processes allows some explanation of the mechanisms of formation dual fuel exhaust emissions. For example, Karim et al [3] found that oxides of nitrogen (NOx) formation is known to be strongly dependent on local temperatures and so most NOx would be formed in the region around the pilot spray where high temperatures exist and the equivalence ratio is close to stoichiometric.…”
Section: Introductionmentioning
confidence: 99%
“…This work showed that for methane substitution levels of up to 50 % (by energy content), the magnitude of initial heat-release peaks at first increase with increasing gaseous-fuel substitution levels (in agreement with [11]). Beyond this 50 % level the results become contradictory, as Pirouzpanah [11] found that initial peaks continued to increase whereas Kishnan et al [13] found them to decrease. The differences are caused by the alternative assumptions made regarding the mass-burning rate.…”
Section: <Figure 1a and 1b>mentioning
confidence: 99%
“…More recently, Kishnan et al [13] returned to Khan's equivalent-fuel definition (similar to [10]) to derive a heat-release rate model that divides the combustion chamber into two zones representing burned and unburned gasses, so that the temperature and mass of each zone can be evaluated simultaneously in addition to the heat-release rate. The mixtures in each zone were assumed to be in thermodynamic equilibrium, with a uniform pressure across the combustion chamber.…”
Section: <Figure 1a and 1b>mentioning
confidence: 99%
See 1 more Smart Citation